A geração de 1870 e a onda positivista - Rosenfield, Luis (2021)
The present thesis seeks to make an in-depth evaluation of the role of positivism as a political project of the so-called Generation of the 1870ies, analyzing how Auguste Comte's ideas were received in Brazil and how positivist philosophy played an important role in the republican movement and in abolitionism, orienting the federalist vindications and the efforts to renew Brazilian history of ideas. Based on the History of Political Philosophy in Brazil, we reconstruct the beginning of the debates about the meaning of positivism in the midnineteenth century and their national outlines from the emergence of the Generation of the 1870ies, up to 1904, the emblematic year of the beginning of the collapse of political positivism after the “Vaccine Uprising”. We seek to trace the spreading of positivism in Brazil and the impact of the positivist ideology on the construction of the Brazilian state and its influence on institutions, investigating them from within the philosophical understanding of the positivist concepts of scientific politics and republican dictatorship. The main instrument for this conceptual reconstruction is Intellectual History, i.e., the presentation of a coherent view of the positivist phenomenon by detailing the main works published during that historical period. It will help us to show the enormous influence of what may truly be considered a positivist wave that swept through Brazil in the last quarter of the 19th century.